Beirut ammonium nitrate explosion: Are not we really learning anything?. Issue 4 (14th October 2020) - Pasman, Hans J.; Fouchier, Charline; Park, Sunhwa; Quddus, Noor; Laboureur, Delphine
Abstract: Disasters caused by large‐scale ammonium nitrate (AN) detonations initiated by fires are well known. The Beirut explosion is again a very sad event with disastrous consequences, but it is not a surprise in the sense of a new phenomenon. It is tragic that calamities with AN occur despite ample guidelines for prevention. Knowledge of the decomposition of AN over the years has greatly progressed, as well how to initiate a detonation with a strong shock wave from a high explosive charge. However, to reproduce the initiation of a detonation by a fire under controlled laboratory conditions never succeeded. The details of the transition of decomposing AN to a detonation remained an open question. Is it a deflagration to detonation mechanism, or is it a shock to detonation one? Knowledge of this may further help process safety measures for the product. The paper will bring research contributions from over a century together, it will develop a scenario how this disaster could happen in Beirut, how much of the AN contributed to the blast, and how further research effort could be beneficial. In addition, the paper estimates the TNT mass equivalent of the AN detonation in Beirut employing three different methods.